2022
DOI: 10.1155/2022/3374780
|View full text |Cite|
|
Sign up to set email alerts
|

Aesthetic Effect of Autologous Fat Transplantation on Frontotemporal Depression Filling and Its Influence on SCL-90 and SES of Patients

Abstract: Objectives. This study aimed to study the aesthetic effect of autologous fat transplantation in frontotemporal depression filling as well as the influence on the Symptom Checklist 90 (SCL-90) and the Rosenberg Self-Esteem Scale (SES) score of patients. Methods. A total of 100 patients with frontotemporal depression admitted to the outpatient department of burn and plastic surgery in our hospital were selected as the observation group, and all of them received autologous fat transplantation. The filling effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%